(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
The purpose of this paper is to explain the process of urbanization in Baja California Sur during the porfirian period, specificaly in San Jose del Cabo, A town, which is located at the southern part of the peninsula. We resumed the idea that urban is a space that is characterized by the existence of a regular merchant trade, political and administrative function and relatively differentiated social organization. The next is divided into four sections where you can see that the urbanization process involved a legal order as the basis of the organization of space and the provision of public services.